Monetary policy regimes and the volatility of long-term interest rates - Virginia Queijo von Heideken (Sveriges Riksbank, 2008)
This paper addresses two important questions that have, so far, been studied separately in the literature. First, the paper aims at explaining the high volatility of long-term interest rates observed in the data, which is hard to replicate using standard macro models. Building a small-scale macroeconomic model and estimating it on U.S. and U.K. data, I show that the policy responses of a central bank that is uncertain about the natural rate of unemployment can explain this volatility puzzle. Second, the paper aims at shedding new light on the distinction between rules and discretion in monetary policy. My empirical results show that using yield curve data may facilitate the empirical discrimination between different monetary policy regimes and that U.S. monetary policy is best understood as originating from a discretionary regime since 1960.
Keywords: C11; C13; C15; E32; E42; E43; E47; E50; 330; long-term interest rates; optimal monetary policy; discretion; commitment; Bayesian estimation; Zins; Volatilität; Geldpolitik; Regelbindung; Diskretionäre Politik; Bayes-Statistik; Großbritannien; USA